2002
DOI: 10.1038/sj.bdj.4801599
|View full text |Cite
|
Sign up to set email alerts
|

A comparative investigation of dental and medical student's motivation towards career choice

Abstract: Objective A number of recent studies have investigated the motivations underlying the career choice of dental and medical students, suggesting that they may be very different. However, as yet, no studies have been conducted which provide a direct comparison of dental and medical students studying in the same place. Accordingly, the aim of this investigation was to conduct a survey which directly compared the motivation of a selection of dental and medical students at Manchester University. Study design A quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
191
2
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(227 citation statements)
references
References 7 publications
30
191
2
4
Order By: Relevance
“…[12][13][14][15][16][17][18] This study found similar motivational factors amongst the cohort, although financial reasons were cited as less important than in some previously published papers. Females tended to favour the statements relating to helping people and working in healthcare, as shown in studies in the USA.…”
Section: Career Selectionmentioning
confidence: 74%
“…[12][13][14][15][16][17][18] This study found similar motivational factors amongst the cohort, although financial reasons were cited as less important than in some previously published papers. Females tended to favour the statements relating to helping people and working in healthcare, as shown in studies in the USA.…”
Section: Career Selectionmentioning
confidence: 74%
“…Similarly to results obtained abroad, the main motivating factors regarding medical profession choice in Hungary remain the personal interest, a sense of profession and an altruistic attitude [8,9]. Among firstyear students however some other factors also became significant.…”
Section: Discussionmentioning
confidence: 97%
“…They compared dental students and general medical students. They found that the latter group showed more pronounced interest in working with people and in scientific achievements [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have generally tried to quantify students' altruism levels (Coulter et al, 2007;Crossley et al, 2002), rather than exploring students' perceptions of altruism and its importance to their practice. As such, this study aimed to address this gap in the literature, by focusing on exploring Leeds' medical students' understandings of altruism and to what extent they felt altruism was part of a doctor's role and identity.…”
Section: Introductionmentioning
confidence: 99%